For Chinese International Students: Stay or Return, That is the Question - Ma, Yingyi; Yang, Chongmin (International Higher Education, 2022)
China continues to send the largest number of international students to America. The question is to what extent Chinese students stay in the United States after completing their education. At the micro level, the answer depends on the level of education and field of study. At the macro level, it depends on US immigration policy and the opportunity structure of the Chinese domestic market.